Faktor-Faktor yang Mempengaruhi Nilai Perusahaan dan Harga Saham Perusahaan Lq45 di Bursa Efek Indonesia - Sherina Donna Clara Pangaribuan; Lasria Sagala; Keumala Hayati; Dio Agung Herubawa (Syntax Literate, 2023)
The Indonesian economy is expected to grow faster in 2016 than the previous year, this is due to investment which is one of the factors that encourage economic growth, Stock prices can be affected by accounting profits where accounting profits that continue to increase can have a positive impact on investors so that investors want to buy these shares. In addition, there are also other factors that can affect stock prices, including accounting profit and operating cash flow. This attracted researchers to further examine the Factors Affecting Share Prices and Company Value in LQ45 Companies on the Indonesia Stock Exchange. The research method used in this study is a documentation method carried out by filtering secondary data such as annual financial statements from the official website of the Indonesia Stock Exchange company and conducting several tests such as classification assumption tests (normality tests, autocorrelation, multicollinearity), hypotheses (stimulant and persial tests). The results of the study found that accounting profit has a negative side to the value of the company and is inversely proportional to the stock price while the operating cash flow affects the value of the company but does not affect the stock price in contrast to investment cash flow where this cash flow does not affect the value of the company or the stock price as well as the laverage which also does not affect both the value of the company and the stock price.